1984
DOI: 10.1007/bf00014876
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of lead and zinc sediment profiles from cores taken by diver and a gravity corer

Abstract: The zinc and lead concentrations were compared in several pairs of sediment cores obtained with a modified K-B corer and by Scuba diver from Coon Lake, Canada . A slow approach to and penetration of the sediments (ca . 0 .1 m s-1 ) was employed for both coring devices . The modified K-B corer gave similar lead and zinc profiles to the diver cores . The divers observed that the K-B corer caused no disturbance of the surface sediment layers as it approached and entered the sediments . These results suggest that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
3
0

Year Published

1985
1985
1994
1994

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 26 publications
1
3
0
Order By: Relevance
“…Lowering the core quickly may reduce compression (Hongve and Erlandsen 1979) but contribute to sediment loss (Baxter et al 198 1). Lowering the corer slowly may help prevent sediment loss (Evans and Lassenby 1984) but accentuate compression (Hongve and Erlandsen 1979). These findings are not new; twofold compression has been observed in much earlier studies as well (Emery and Dietz 194 1;Emery and Hulsemann 1964).…”
supporting
confidence: 52%
See 1 more Smart Citation
“…Lowering the core quickly may reduce compression (Hongve and Erlandsen 1979) but contribute to sediment loss (Baxter et al 198 1). Lowering the corer slowly may help prevent sediment loss (Evans and Lassenby 1984) but accentuate compression (Hongve and Erlandsen 1979). These findings are not new; twofold compression has been observed in much earlier studies as well (Emery and Dietz 194 1;Emery and Hulsemann 1964).…”
supporting
confidence: 52%
“…Other studies have reported little or no significant loss of surficial sediments when lowering the corer at high speed into clayrich sediments (Leonard 1990) and when coring by a slow coring method with a K-B corer (which does not impede flow of water through the core top) without a core catcher (Evans and Lassenby 1984). Bopp and Simpson (1989) often found measurable 'Be (half-life = 54 d) in gravity cores from the Hudson River, suggesting no loss of core top in those sediments of 50-70% porosity.…”
mentioning
confidence: 98%
“…7) demonstrates the importance of careful, slow, lowering of the sampler. Recent studies by Evans (1982) and Evans & Lasenby (1984) give additional support to this statement. Previously, free-fall distances of 1-3 m for core samplers have been proposed as desirable (Hvorslev & Stetson, 1946;Kullenberg, 1955;Burns, 1966).…”
Section: Methodsmentioning
confidence: 77%
“…All cores 6163-15 cm long) were collected in Pyrex core tubes 67.0 cm i.d., 20 cm long) using a K.B. corer (Brinkhurst et al 1969) and a slow approach technique which mininaized disturbance (Evans and Lasenby 1984). Within 6 h of coring, the sediment Garas pushed up slowly so that the surface was level with the top of each core tknbe, and the cores were submerged in a storage bath kept at the temperature in situ.…”
Section: Methodsmentioning
confidence: 99%